Upaya Mengatasi Permasalahan Lead Time Pembelian di PT. X - Monica Iko Marita; Herri Christian Palit (Jurnal Titra, 2021)
PT. X is a manufacturing company engaged in the production of cosmetic packaging. This study focuses on the purchasing process in the Purchasing Department. The problem faced by the Purchasing Department is the lead time for submitting a purchase requisition (PR) to making a purchase order (PO). The standard set by the company is four days. From 2018 to January 2021, 28.45% of purchases did not meet lead time standards. Improvement efforts made were Data Cleaning, naming standardization, making part numbers, submitting PR using email, updating PR forms, and inventory management. After making efforts to improve the percentage of purchase lead times that exceed the four-day span in the PR to PO process, it is 10.89% in February to May 2021. The decrease obtained from the improvements made is 17.55%.